ANALISIS KEMAMPUAN PEMECAHAN MASALAH DALAM MENGERJAKAN SOAL CERITA MATERI PECAHAN BERDASARKAN TEORI POLYA PADA SISWA KELAS V SD NEGERI SIGENUK KABUPATEN PURWOREJO - Maria Melinda; Yuli Widiyono; Titi Anjarini (STKIP Subang, 2024)
This research aims to analyze the mathematical problem solving abilities of fraction material based on Polya theory in fifth grade students at Sigenuk State Elementary School, Purworejo Regency.This type of research is descriptive research with a qualitative approach. The research subjects consisted of 6 students in the high, medium and low categories. The data collection techniques used consisted of written tests, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The research results show that: (1) students in the high category are able to understand the problem, plan a solution to the problem, carry out the solution plan, and recheck the answers according to the Polya stages. (2) Students in the medium category are only able to understand the problem, plan and implement the problem solving plan, but are unable to double check the answers. (3) Students in the low category are only able to understand the questions, are unable to make plans, are unable to implement plans, and are not able to check their answers again.